Combined membrane aeration and membrane filtration for space-efficient nitrogen control in reuse-oriented biological pretreatment - Hsin-Chieh Lin; Ting-Wei Wu; Yu-Tzu Huang; Ho Kyong Shon; Chia-Hung Hou (Desalination, 2026)

Fibrotic microRNAs in the suppression of HSC activation and ECM deposition to facilitate the regression of hepatic fibrosis in zebrafish - Yu-Heng Lai; Mu-Kuang He; Chung-Tsui Huang; Han-Yu Tseng; Tzu-Ching Lin; Ting-Yu Yang; Semon Wu; Guor Mour Her (Journal of Molecular Medicine, 2026)
During liver injury, early pathological changes may go unnoticed, delaying the diagnosis until the disease has advanced to stages such as fibrosis, cirrhosis, or hepatocellular carcinoma. Hepatic fibrosis is a sign of long-term liver injury that leads toward permanent liver damage. It involves the buildup of too much extracellular matrix (ECM) and is activated by hepatic stellate cells (HSCs). The transforming growth factor-β1 (TGF-β1)/SMAD pathway is central to this process, which shows great potential for therapeutic strategies. Therefore, we investigated the therapeutic potential of microRNA (miRNA)-mediated regulation of fibrogenesis by using zebrafish models. A group of fibrosis-related miRNAs was identified and used to generate transgenic zebrafish lines. Fibrosis was induced via doxycycline (DOX)-controlled overexpression of TGF-β1a, and the antifibrotic efficacy of miRNAs was evaluated. Quantitative real-time PCR showed a marked downregulation of the target miRNAs, accompanied by decreased expression of fibrotic markers. Next, we confirmed that TGF-β1a, GREM1, and α-SMA protein levels were decreasing. Histological staining revealed improved liver structure and diminished collagen deposition. These findings indicate that through manipulating the miRNA expressions, we can effectively disrupt TGF-β-induced fibrogenesis, inactivate HSC, inhibit ECM remodeling, and attenuate liver fibrosis, and highlight the potential of miRNA-based therapeutic strategies for early intervention in liver disease. Key messages Establishment of an in vivo model for developing an inducible miRNA expression system in zebrafish. Predicting and evaluating targeted miRNAs that attenuate TGF-β-induced hepatic fibrosis. Elucidate the potential mechanism for fibrosis that may be a strategy for future therapies. Graphical Abstract MicroRNA-mediated modulation attenuates hepatic fibrosis by coordinately suppressing the TGF-β/SMAD signaling pathway, hepatic stellate cell activation, and extracellular matrix deposition. Protein-level validation confirms reduced phosphorylation of Smad2 and decreased expression of key fibrotic markers, including α-SMA, collagen I, and fibronectin. These findings highlight a multi-target regulatory mechanism through which miRNAs exert antifibrotic effects at the systems level.

Biochar-based cathodes for bioelectro-Fenton systems: Design strategies, electrocatalytic mechanisms, and environmental applications - Shu-Hui Liu; Chung-Yen Yeh; Wei-Tzu Huang; Yi-Chun Yu; Chi-Wen Lin (Journal of Environmental Chemical Engineering, 2026)

Synergistic modulation of nickel–manganese glycerate via sequential sulfurization and oxidation for high-performance battery–supercapacitor hybrids - Tsung-Rong Kuo; Lu-Yin Lin; Tzu-Han Chou; You-Zher Yu; Chutima Kongvarhodom; Sibidou Yougbaré; Muhammad Saukani; Hung-Ming Chen (Journal of Environmental Chemical Engineering, 2026)

Pyridoxine and valproic acid co-exposure induces ER-mediated calcium dysregulation and cardiac toxicity in zebrafish - Wei-Hsiang Chen; Po-Yuan Chen; Wen-Yu Chung; Tein-Yu Chiu; Wei-Ling Lin; Chen-Yu Huang; Hui-Hua Chang; Chin-Wei Huang; Bing-Hung Chen; Lin Kang; Tzu-Fun Fu (Chemico-Biological Interactions, 2026)

Immediate effects of binaural beat stimulation on prefrontal cortical activation after cycling exercise: an electroencephalography-based study - Shih-Fen Hsiao; Tzu-Ling Liu; Yu-Chen Lin; Chen-Wen Yen; Ka-Chun Siu; Jau-Hong Lin (Experimental Brain Research, 2026)

Electrochemically functionalized MWCNT|ABTS nanocomposite: A versatile platform for dye recovery and upcycling for detection and valorization of nitroaromatics - Fitri Nur Indah Sari; Tien-Yu Kuo; Tzu-Hsuan Wang; Eunice Estrella De Guzman; Chia-Yu Lin (Journal of Environmental Chemical Engineering, 2026)

Dynamic electronic and spin-state modulations of ternary single-atom catalysts for ultrahigh power density and ultra-stable rechargeable zinc-air batteries - Yu-Chieh Ting; Shao-I Chang; Kai-An Lee; Chiung-Wen Chang; Tzu-Hsiang Lin; Chih-Heng Lee; Hsin-Yi Tiffany Chen; Shih-Yuan Lu (Chemical Engineering Journal, 2026)

Prioritizing key determinants of hematite photocatalysis through structure – Property contour mapping and statistical correlation analysis - TsingHai Wang; Ching-Lung Chen; Wei-Fan Kuan; Wei-Tong Li; Ching-Yao Ke; Tzu-Han Lin; Chung-Yu Guan; Huei-Ru Fuh (Process Safety and Environmental Protection, 2026)

Metabolomics-based investigation of PFOS-induced molecular perturbations across multiple rat organs - Tzu-Hsin Yen; Sheng-Han Lee; Hao-Jan Liang; Zou-Xiao Huang; Chi-Tsung Chen; Christopher Li; Ching-Yu Lin (Environmental Toxicology and Pharmacology, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

AMPK Activation by ENERGI Ameliorates Behavioral and Synaptic Deficits in a Mouse Model of Autism - Ming-Chia Chu; Chi-Chun Wu; Yueh-Jung Chung; Chieh-Yu Chang; Han-Fang Wu; Sze-Chi Tsai; Tzu-Ning Peng; Tzu-Jung Yang; Hui-Ching Lin (Molecular Neurobiology, 2026)
Autism spectrum disorder (ASD), a neurodevelopmental disorder, is characterized by synaptic dysregulation as its underlying pathophysiological mechanism. AMP-activated protein kinase (AMPK), an intracellular energy sensor, plays a pivotal role in regulating synaptic integrity and function. Current treatments for ASD exhibit limited benefits in alleviating the core symptoms of ASD. Consequently, we investigated the therapeutic potential of ENERGI, a novel AMPK-activating compound, in a valproate (VPA)-induced mouse model of ASD. ENERGI was administered via drinking water to VPA-induced ASD offspring. After 7 days of treatment, ENERGI gradually alleviated social defects, repetitive behaviors, and emotional comorbidities in VPA-induced ASD offspring. At the synaptic level, ENERGI treatment restored aberrant plasticity, spine structure, and dendritic arborization in the hippocampus of VPA-induced ASD offspring. Notably, the curative effects of ENERGI in VPA-induced ASD offspring were equivalent to those of D-cycloserine (DCS), a known therapeutic candidate for ASD. Moreover, ENERGI demonstrated superior efficacy in restoring spine abnormalities than DCS. Mechanistically, 7-day ENERGI treatment reversed the reduction in AMPK phosphorylation, and normalized the elevated PSD95 and synaptic GluA2 levels in VPA-induced ASD offspring, whereas DCS treatment only rescued the synaptic GluA2 levels. Overall, these findings suggest that AMPK activation by ENERGI effectively reverses behavioral and synaptic deficits in a preclinical ASD model, supporting AMPK as a promising target for developing novel ASD therapies.

Transforming gastrointestinal health with probiotic fermented milk: a systematic review and meta-analysis - Ngan Thi Kim Nguyen; Yu-Hsin Chang; Lee-Yuan Lin; Philippe Noirez; Roma Panwar; Tzu-Wen L. Cross; Nguyen-Phong Vo; Shyh-Hsiang Lin (International Dairy Journal, 2025)

The influence of trees shade level on human thermal comfort and the development of applied assessment tools - Yu-Ying Wei; Ching-Yin Cheng; Tzu-Ping Lin (Landscape and Urban Planning, 2025)

Effective peroxymonosulfate activation over cobalt oxide (CoO)/nitrogen-doped graphene aerogel for rhodamine b degradation - Xian-Lun Liao; Dhayanantha Prabu Jaihindh; Tzu-Ting Chang; Yi-Feng Lin; Wei-Hung Chiang; Yu-Chun Wang (Journal of Water Process Engineering, 2025)

Description of Fulverythrobacter ferritrahens gen. nov., sp. nov., a Siderophore-Producing Bacterium Isolated from Poultry Manure Compost and Reclassification of Caenibius fulvus and Altererythrobacter segetis as Fulverythrobacter fulvus Comb. nov. and Croceibacterium segetis Comb. nov. - Shih-Yao Lin; Asif Hameed; Tzu-Yu Lin; Chiu-Chung Young (Current Microbiology, 2025)

Temporal variability of greenhouse gas fluxes in monoculture of tilapia in ponds - Yi–Jung Chen; Han–Yang Yeh; Chien-Wei Tu; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; Ruei-Feng Shiu; Tzu-Ning Teng; Meng–Chou Lee; Fan–Hua Nan (Aquaculture International, 2025)

Estimating and classifying urban carbon budget based on land use intensity with regulatory strategies developing - Li-tzu Yu; Cing Chang; Tzu-Ping Lin (Sustainable Cities and Society, 2025)

Waste valorization into K-doped alumina catalysts via Al-MOF templates for efficient COS hydrolysis - Jia-Yin Lin; Jia-Yu Lee; Pei-Tzu Chang; Chih-Ying Wang (Journal of Environmental Chemical Engineering, 2025)

System temperature prediction and verification of all-sky electrostatic analyzer on the lunar surface - Tsung-Pin Hung; Chih-Yu Chiang; Tzu-Fang Chang; Zhao-Yu Huang; Yu-Rong Cheng; Sheng-Cheng Tsai; Tzu-En Yen; Jih-Run Tsai; Shin-Fa Lin (Advances in Space Research, 2025)

Alisertib inhibits acute myeloid leukemia cell growth by inhibiting STAT3 activation - Pang-Ting Cheng; Ho Lin; Yu-Chiao Cheng; Tzu-Hung Hsiao; Pei-Pei Jhan; Jia-Rung Tsai; Mei-Chih Chen; Tai-Lin Chen; Chieh-Lin Jerry Teng (Toxicology and Applied Pharmacology, 2025)

Causes, emission characteristics, and health risks of persistent free radicals and reactive oxygen species in PM2.5 produced by smoldering incense - Yu-Chieh Wang; Bo-Yu Chen; Yen-Hsien Li; Tzu-Hsien Tseng; Chon-Lin Lee; Wei-Min Ching (Atmospheric Pollution Research, 2025)

Methane dynamics controlled by subsurface metabolic architecture and tidal cycling in a mangrove wetland - Tzu-Hsuan Tu; Tai-Yi Lee; Zih-Huei Yu; Chun-Hung Lu; Yueh-Ting Lin; Pei-Ling Wang (Science of The Total Environment, 2025)

CCN1 Is a Therapeutic Target for Reperfused Ischemic Brain Injury - Gilbert Aaron Lee; Yu-Wei Chang; Jing-Huei Lai; Tzu-Hao Chang; Shiu-Wen Huang; Chih‑Hao Yang; Ting-An Shen; Wan-Li Lin; Ying-Chieh Wu; Li-Wen Tseng; Sung-Hui Tseng; Yung-Chieh Chen; et al. (Translational Stroke Research, 2025)

Challenges and opportunities in using biowaste for sustainable hydroponic netted melon (Cucumis melo L.) cultivation - Yen-Tzu Fan; Zih-Ee Lin; Pei-Te Chiueh; Yu-Pin Lin; Lien-Chieh Cheng; Yu-Shen Cheng; Shu-I Lin; Chihhao Fan (Agricultural Systems, 2025)

Reversing Neuronal Klotho Dysfunction–Mediated Diabetic Neuropathy Through 16:8 Intermittent Fasting - Ying-Shuang Chang; Yu-Yu Kan; Tzu-Ning Chao; Yi-Hsuan Chen; Yu-Lin Hsieh (Molecular Neurobiology, 2025)

The influence of shading facilities on outdoor thermal comfort, pedestrian walking speed, and indoor satisfaction - Zi-En Lin; Shiang-Yu Wang; Kuo-An Hung; Chiao-Jou Hsieh; Tzu-Ping Lin (International Journal of Biometeorology, 2025)

An injectable in situ-forming hydrogel with self-activating genipin-chitosan (GpCS) cross-linking and an O2/Ca2+ self-supplying capability for wound healing and rapid hemostasis - Chi Lin; Tzu-Wei Lu; Fang-Yu Hsu; Tzu-Wen Huang; Ming-Hua Ho; Hsien-Tsung Lu; Fwu-Long Mi (Carbohydrate Polymers, 2025)

Decreases in pH from effluent had a devastating but reversible impact on the coastal plankton communities - Yu-Jia Lin; Tzu-Chun Chen; Chen-Tung Arthur Chen; Saou-Lien Wong; Pei-Jie Meng; Meng-Hsien Chen (Marine Pollution Bulletin, 2025)

Methane Index and TEX86 values in cold seep sediments: Implications for paleo-environmental reconstructions - Sze Ling Ho; Yu-Shih Lin; Pei-Ling Wang; Tzu-Ting Chen; Pei-Ting Lee; Hui-Hsin Wang; Tzu-Jung Cheng; Yun-Ju Wang; Chih-Chieh Su; Min-Te Chen (Geochimica et Cosmochimica Acta, 2025)

Optimizing sediment control by adjusting the relative spacing between trusses/beams in an open-type check dam - Hung-En Chen; Tzu-Yu Chen; Ya-Lin Zheng; Yen-Yu Chiu; Su-Chin Chen (Landslides, 2025)

Combining geographic information and climate data to develop urban building energy prediction models in Taichung, Taiwan - Cing Chang; Chieh-Yu Chen; Tzu-Ping Lin (Sustainable Cities and Society, 2024)

Quantifying the effects of the microphysical hygroscopic restructuring of soot on ensemble optical properties and satellite aerosol optical depth retrievals - Kuo-En Chang; Tang-Huang Lin; Ta-Chih Hsiao; Yi-Ling Chang; Tzu-Chi Lin; Chih-Yu Chan; Charles C.-K. Chou (Science of The Total Environment, 2024)

Di(2-ethylhexyl) phthalate disrupts circadian rhythm associated with changes in metabolites and cytochrome P450 gene expression in Caenorhabditis elegans - Pei-Ling Yen; Ting-An Lin; Chun-Han Chang; Chan-Wei Yu; Yu-Hsuan Kuo; Tzu-Ting Chang; Vivian Hsiu-Chuan Liao (Environmental Pollution, 2024)

Coral mariculture using abandoned abalone farming ponds in northeastern Taiwan - Shinya Shikina; Yin-Chu Cheng; Tzu-Chieh Lin; Yu-En Chang; Pin-Hsuan Tsai; Emma Chen; Yu-Chuan Chang; Yuen-Yi Leung; Yi-Chun Yu; Yi-Ling Chiu (Aquaculture, 2024)

Effects of physical sterilization on microbial safety, nutritional composition, and antioxidant activity of queen bee larva powder, a by-product of royal jelly production - Yu-Hsin Chen; Jer-An Lin; Chi-Chung Peng; Pei-Shou Hsu; Tzu-Hsien Wu; Yen-Hou Chen; Ming-Cheng Wu (Food Control, 2024)

Dual-Salt aqueous electrolyte for enhancing Charge-Storage properties of VO2 polymorphic cathodes for Zn-Ion batteries - Jing-Hong Huang; Xu-Feng Luo; Tzu-Yu Kuo; Yu-Hua Lai; Purna Chandra Rath; Chun-Wei Huang; Ming-Hsien Lin; An-Yuan Hou; Ju Li; Yu-Sheng Su; Wen-Wei Wu; Jeng-Kuei Chang (Chemical Engineering Journal, 2024)

Targeting TGFβ receptor-mediated snail and twist: WSG, a polysaccharide from Ganoderma lucidum, and it-based dissolvable microneedle patch suppress melanoma cells - Hung-Chih Lo; Tzu-En Lin; Che-Yu Lin; Wei-Hao Wang; Yu-Chen Chen; Pei-Hsien Tsai; Jung-Chen Su; Mei-Kuang Lu; Wei-Hung Hsu; Tung-Yi Lin (Carbohydrate Polymers, 2024)

Description of Aliirhizobium terrae sp. nov., A Plant Growth-Promoting Bacterium Isolated from a Maize-Rice Rotation Agriculture Field - Shih-Yao Lin; Tzu-Yu Lin; Asif Hameed; Chia-Fang Tsai; Chiu-Chung Young (Current Microbiology, 2024)

The application of a high-density street-level air temperature observation network (HiSAN): Spatial and temporal variations of thermal and wind condition in different climatic condition types - Yu-Cheng Chen; Kai-Shan Hou; Yu-Jie Liao; Tsuyoshi Honjo; Fang-Yi Cheng; Tzu-Ping Lin (Sustainable Cities and Society, 2024)

Association among polydisperse aerodynamic size of bioaerosols, biodiversity and urbanization in kindergartens - Tzu-Hsien Lin; Ying-Hsiang Chou; Tzu-Yu Hsu; Chun-Hui Hung; Chane-Yu Lai (Chemosphere, 2024)

Urine cadmium and urolithiasis: A systematic review and meta-analysis - Yuan-Hsin Chen; Chih-Fu Wei; Ya-Yun Cheng; Carol Mita; Chinh Lu Duc Hoang; Cheng-Kuan Lin; Yu-Tzu Chang; David C. Christiani (Environmental Research, 2024)

Assessment of PM2.5-associated mortality burden among the elderly: Insights into demographic, socio-economic, and geographic factors - Ayushi Sharma; Hsi-yu Hsiao; Jia-Yi Liu; Shih-Chun Candice Lung; Huey-Jen Su; Ching-Fen Shen; Nai-Tzu Chen; Pei-Chih Wu; Cheng-Yu Lin; Sheng-Fu Liang; Tain-Junn Cheng; Ta-Chien Chan; et al. (Air Quality, Atmosphere & Health, 2024)

Isolation of 24-homoscalarane sesterterpenoids from a sponge of the genus Lendenfeldia - Li-Guo Zheng; You-Yan Chen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yi-Hao Lo; Yu-Chi Tsai; Hao-Chun Hu; You-Ying Chen; Tsong-Long Hwang; Tzu-Ming Ou; Ping-Jyun Sung (Phytochemistry Letters, 2024)

Species selection as a key factor in the afforestation of coastal salt-affected lands: Insights from pot and field experiments - Tzu-Hao Su; Yang Shen; Yao-Yu Chiang; Yu-Ting Liu; Han-Ming You; Hung-Chih Lin; Kuan-Ning Kung; Yao-Moan Huang; Chih-Ming Lai (Journal of Environmental Management, 2024)

Examining arterial pulsation to identify and risk-stratify heart failure subjects with deep neural network - Chieh-Chun Huang; Shih-Hsien Sung; Wei-Ting Wang; Yin-Yuan Su; Chi-Jung Huang; Tzu-Yu Chu; Shao-Yuan Chuang; Chern-En Chiang; Chen-Huan Chen; Chen-Ching Lin; Hao-Min Cheng (Physical and Engineering Sciences in Medicine, 2024)
Hemodynamic parameters derived from pulse wave analysis have been shown to predict long-term outcomes in patients with heart failure (HF). Here we aimed to develop a deep-learning based algorithm that incorporates pressure waveforms for the identification and risk stratification of patients with HF. The first study, with a case–control study design to address data imbalance issue, included 431 subjects with HF exhibiting typical symptoms and 1545 control participants with no history of HF (non-HF). Carotid pressure waveforms were obtained from all the participants using applanation tonometry. The HF score, representing the probability of HF, was derived from a one-dimensional deep neural network (DNN) model trained with characteristics of the normalized carotid pressure waveform. In the second study of HF patients, we constructed a Cox regression model with 83 candidate clinical variables along with the HF score to predict the risk of all-cause mortality along with rehospitalization. To identify subjects using the HF score, the sensitivity, specificity, accuracy, F1 score, and area under receiver operating characteristic curve were 0.867, 0.851, 0.874, 0.878, and 0.93, respectively, from the hold-out cross-validation of the DNN, which was better than other machine learning models, including logistic regression, support vector machine, and random forest. With a median follow-up of 5.8 years, the multivariable Cox model using the HF score and other clinical variables outperformed the other HF risk prediction models with concordance index of 0.71, in which only the HF score and five clinical variables were independent significant predictors (p < 0.05), including age, history of percutaneous coronary intervention, concentration of sodium in the emergency room, N -terminal pro-brain natriuretic peptide, and hemoglobin. Our study demonstrated the diagnostic and prognostic utility of arterial waveforms in subjects with HF using a DNN model. Pulse wave contains valuable information that can benefit the clinical care of patients with HF.

Critical roles of tubular mitochondrial ATP synthase dysfunction in maleic acid-induced acute kidney injury - Hugo Y.-H. Lin; Chan-Jung Liang; Ming-Yu Yang; Phang-Lang Chen; Tzu-Ming Wang; Yen-Hua Chen; Yao-Hsiang Shih; Wangta Liu; Chien-Chih Chiu; Chih-Kang Chiang; Chang-Shen Lin; Han-Chen Lin (Apoptosis, 2024)
Maleic acid (MA) induces renal tubular cell dysfunction directed to acute kidney injury (AKI). AKI is an increasing global health burden due to its association with mortality and morbidity. However, targeted therapy for AKI is lacking. Previously, we determined mitochondrial-associated proteins are MA-induced AKI affinity proteins. We hypothesized that mitochondrial dysfunction in tubular epithelial cells plays a critical role in AKI. In vivo and in vitro systems have been used to test this hypothesis. For the in vivo model, C57BL/6 mice were intraperitoneally injected with 400 mg/kg body weight MA. For the in vitro model, HK-2 human proximal tubular epithelial cells were treated with 2 mM or 5 mM MA for 24 h. AKI can be induced by administration of MA. In the mice injected with MA, the levels of blood urea nitrogen (BUN) and creatinine in the sera were significantly increased ( p p p p p p

Implementing policies to mitigate urban heat islands: Analyzing urban development factors with an innovative machine learning approach - Shiang-Yu Wang; Hsing-Yu Ou; Ping-Chun Chen; Tzu-Ping Lin (Urban Climate, 2024)

3D-printed Al2O3 framework supported carbon-bridged tri-s-triazine of g-C3N4 for photocatalytic tetracycline oxidation - Chechia Hu; Lee-Lee Chang; Wei Chen; Wan-Yuan Hsu; Szu-Chia Chien; Chien-Hua Chen; Yu-Ting Lin; Tzu-Jung Hsu; Kuo-Lun Tung (Chemical Engineering Journal, 2024)

Extinction coefficient of dry and deliquescent chemical components of PM_(2.) 5 in urban areas and their impacts on visibility deterioration - Chien-Hao Lin; Shao-En Sun; Chung-Te Lee; Ting-Yu Chiang; Shih-Yu Chang; Tzu-Shuan Wu; Hsin-Yu Wei; Ling-Ya Chen; Hao-Wei Liu; Sally C.W. Tai (Atmospheric Pollution Research, 2024)

Roles of Neuronal Protein Kinase Cε on Endoplasmic Reticulum Stress and Autophagic Formation in Diabetic Neuropathy - Yu-Yu Kan; Ying-Shuang Chang; Wen-Chieh Liao; Tzu-Ning Chao; Yu-Lin Hsieh (Molecular Neurobiology, 2024)
In chronic diabetic neuropathy (DN), the cellular mechanisms of neuropathic pain remain unclear. Protein kinase C epsilon (PKCε) is an intracellular signaling molecule that mediates chronic pain. This paper addresses the long-term upregulated PKCε in DN associated with endoplasmic reticulum (ER) stress and autophagic formation and correlates to chronic neuropathic pain. We found that thermal hyperalgesia and mechanical allodynia course development were associated with PKCε upregulation after DN but not skin denervation. Pathologically, PKCε upregulation was associated with the expression of inositol-requiring enzyme 1α (IRE1α; ER stress–related molecule) and ubiquitin D (UBD), which are involved in the ubiquitin-proteasome system (UPS)-mediated degradation of misfolded proteins under ER stress. Manders coefficient analyses revealed an approximately 50% colocalized ratio for IRE1α(+):PKCε(+) neurons (0.34–0.48 for M1 and 0.40–0.58 for M2 Manders coefficients). The colocalized coefficients of UBD/PKCε increased (M1: 0.33 ± 0.03 vs. 0.77 ± 0.04, p < 0.001; M2: 0.29 ± 0.05 vs. 0.78 ± 0.04; p < 0.001) in the acute DN stage. In addition, the regulatory subunit p85 of phosphoinositide 3-kinase, which is involved in regulating insulin signaling, exhibited similar expression patterns to those of IRE1α and UBD; for example, it had highly colocalized ratios to PKCε. The ultrastructural examination further confirmed that autophagic formation was associated with PKCε upregulation. Furthermore, PKCεv1-2, a PKCε specific inhibitor, reverses neuropathic pain, ER stress, and autophagic formation in DN. This finding suggests PKCε plays an upstream molecule in DN-associated neuropathic pain and neuropathology and could provide a potential therapeutic target.

Impact of occupational noise exposure on the hearing level in hospital staffs: a longitudinal study - Tang-Chuan Wang; You-Cheng Yu; Alan Hsu; Jia-Yi Lin; Yung-An Tsou; Chiu-Shong Liu; Kai-Jen Chuang; Wen-Chi Pan; Chin-An Yang; Sung-Lin Hu; Chien-Yi Ho; Tzu-Liang Chen; et al. (Environmental Science and Pollution Research, 2024)

Photo-protection and photo-inhibition during light induction in Barbula indica and Conocephalum conicum under different light gradients - Chung-I. Chen; Kuan-Hung Lin; Meng-Yuan Huang; Kuei-Yu Yao; Chau-Ching Huang; Tzu-Chao Lin; En-Liang Chu; Jia-Dong Yang; Ching-Wen Wang (Photosynthesis Research, 2024)

Efficient and cost-effective method for identifying urban ventilation corridors using a heuristic search algorithm - Tsz-Kin Lau; Pei-Chi Tsai; Hsing-Yu Ou; Tzu-Ping Lin (Sustainable Cities and Society, 2024)

GW4064 inhibits migration and invasion through cathepsin B and MMP2 downregulation in human bladder cancer - Chien-Chang Kao; Chien-Rui Lai; Yi-Hsuan Lin; Tzu-Min Chen; Yu-Ling Tsai; Wen-Chiuan Tsai; Tze-Yun Ong; Hisao-Hsien Wang; Sheng-Tang Wu; Ying Chen (Chemico-Biological Interactions, 2024)

Biological upgrading of biogas assisted with membrane supplied hydrogen gas in a three-phase upflow reactor - Yue Rao; Tzu-Yu Lin; Fangqiong Ling; Zhen He (Bioresource Technology, 2024)

A numerical investigation of an indoor dry storage facility on heat transfer - Chia-Wei Lin; Yung-Shin Tseng; Kai-Qi Lin; Yu-Hsuan Chang; Tzu-Chen Hung; Hua-Yi Hsu (Annals of Nuclear Energy, 2024)

Linkage analysis for water-energy-economic system efficiency in China - Zhong Fang; Yung-ho Chiu; Yiqin Chen; Tai-Yu Lin; Tzu-Han Chang (Environment, Development and Sustainability, 2024)

Evaluating the toxic mechanism of 1,2-diacetylbenzene in neural cells/tissues: The favorable impact of silibinin - Li-Yu Fay; Jun-Yi Chien; Ching-Feng Weng; Huai-Sheng Kuo; Dann-Ying Liou; Wei-Hao Weng; Chi-Hung Lin; Ya-Tzu Chen; Wen-Hung Huang; Wen-Cheng Huang; May-Jywan Tsai; Henrich Cheng (NeuroToxicology, 2023)

Application of local climate zones combined with machine learning to predict the impact of urban structure patterns on thermal environment - Tsz-Kin Lau; Yu-Cheng Chen; Tzu-Ping Lin (Urban Climate, 2023)

Associations between parental and postnatal metal mixture exposure and developmental delays in a Taiwanese longitudinal birth cohort of preschool children - Chi-Sian Kao; Yen-Tzu Fan; Ying-Lin Wang; Yi-Hua Chen; Hsing-Jasmine Chao; Yu-Chun Lo; Chuen-Bin Jiang; Ling-Chu Chien (Environmental Science and Pollution Research, 2023)

Using drone soundings to study the impacts and compositions of plumes from a gigantic coal-fired power plant - Yen-Chen Chen; Jia-Lin Wang; Chih-Yuan Chang; Ming-Tung Chuang; Charles C.-K. Chou; Xiang-Xu Pan; Yu-Jui Ho; Chang-Feng Ou-Yang; Wen-Tzu Liu; Chih-Chung Chang (Science of The Total Environment, 2023)

The biocompatibility and hemostatic efficacy of silk fibroin nanofibrils fabricated by Shear-Induced phase separation process - Po-Wen Lu; Yu-Tzu Wu; Liang-Yu Chang; Tzu-Wei Lu; Chonlachat Jaihao; Ching-Shuan Huang; Mo-Fei Murphy Chuang; Chunche Lin; Innie Chen; Agnese Brangule; Aleksej Zarkov; Aivaras Kareiva; et al. (Chemical Engineering Journal, 2023)

Profit-seeking enterprise production and business waste treatment efficiency in Taiwan - Tai-Yu Lin; Yung-Ho Chiu; Yi-Nuo Lin; Tzu-Han Chang (Environment, Development and Sustainability, 2023)

Validation of 16S rRNA gene sequencing and metagenomics for evaluating microbial immigration in a methanogenic bioreactor - Tzu-Yu Lin; Wen-Tso Liu (Water Research, 2023)

Investigation of the fall armyworm (Spodoptera frugiperda) gut microbiome and entomopathogenic fungus-induced pathobiome - Yao-Chia Liu; Tzu-Han Chen; Yu-Feng Huang; Chang-Lin Chen; Yu-Shin Nai (Journal of Invertebrate Pathology, 2023)

Temporal transition trends of cord blood lead levels in various human development index countries and in the Taipei metropolitan area - Yaw-Huei Hwang; Hui-Chu Wu; Ming-Kwang Shyu; Chien-Nan Lee; Shin-Yu Lin; Pau-Chung Chen; Hung-Yi Chuang; Pei-Wen Lin; Tso-Hsien Wu; Yen-Tzu Chen (Environmental Pollution, 2023)

Effects of orientation and dimensions of shading structures on thermal comfort - Hsing-Yu Ou; Tzu-Ping Lin (Building and Environment, 2023)

Harnessing split fluorescent proteins in modular protein logic for advanced whole-cell detection - Ping-Heng Lin; Ssu-Tzu Tsai; Yu-Chia Chang; Yi-Ju Chou; Yi-Chun Yeh (Analytica Chimica Acta, 2023)

The association of bisphenol A and paraben exposure with sensorineural hearing loss in children - Chia-Huang Chang; Chun-Ting Lu; Tai-Ling Chen; Wen-Tzu Huang; Pao-Chuan Torng; Chen-Wei Chang; Yu-Chun Chen; Yu-Lin Yu; Yung-Ning Chuang (Environmental Science and Pollution Research, 2023)

Culturing reef-building corals on a laboratory dish: a simple experimental platform for stony corals - Shinya Shikina; Tzu-Chieh Lin; Yu-Ling Chu; Yin-Chu Cheng; Yu-En Chang; Naohisa Wada; Sen-Lin Tang; Yoshiyuki Iizuka; Yi-Ling Chiu (Frontiers in Marine Science, 2023)
Development and maintenance of coral reef ecosystems rely on daily micro-biological activities of healthy corals. Although a comprehensive understanding of coral biological properties, as well as factors negatively affecting coral growth, are essential to conserve existing corals, the current lack of a tractable culture and experimental platform has delayed acquisition of such knowledge. Here we show a highly versatile culture system, “coral-on-a-laboratory dish” (CLD), allowing long-term culturing of various corals in plastic/glass Petri dishes with maintenance of their biological properties. Under optimized conditions, coral microcolonies (~5 mm x 5 mm fragments) of Pocillopora damicornis were cultured for several months in dishes with high survivorship and characteristic growth. These microcolonies maintained their biological properties, such as reproduction, skeleton formation, coral-algal symbiosis, ingestion, and digestion. Thus far, CLD has been used to maintain at least 4 other coral species from 4 other families, including the Acroporidae, the Pocilloporidae, the Poritidae, and the Merulinidae for more than 2 months with 100% survivorship. CLD is applicable to a variety of biophysiological studies, including coral-algal symbiosis and impact assessment of marine pollutants, e.g., a sunscreen substance, oxybenzone, and an organic biocide, Irgarol 1051, at cellular-level resolution. The CLD platform, which allows easy and inexpensive coral maintenance in a laboratory incubator, represents a technological breakthrough that will greatly advance coral studies.

Influence of microclimate control on the growth of asparagus under greenhouse in tropical climates - Kuo-An Hung; Yi-Wei Hsu; Yu-Cheng Chen; Tzu-Ping Lin (International Journal of Biometeorology, 2023)

Analysis of natural disasters and energy efficiency in China - Zhong Fang; Yung-ho Chiu; Tai-Yu Lin; Tzu-Han Chang; Yi-Nuo Lin (Environment, Development and Sustainability, 2023)

Modeling of an integrated H2S/NH3 scrubber and regeneration columns for coke oven gas purification - Hao-Jen Pan; Ming-Chun Fang; Jeffrey D. Ward; Hao-Yeh Lee; Hsun-Yu Lin; Cheng-Ting Hsieh; Chih-Lung Lee; Tzu-Hsien Huang; Yu-Chen Hsieh; Shih-Chieh Lin; Wei-Ti Chou (Journal of Cleaner Production, 2023)

Greenhouse gas emission indicators, energy consumption efficiency, and optimal carbon emission allowance allocation of the EU countries in 2030 - Tai-Yu Lin; Yung-Ho Chiu; Yi-Nuo Lin; Tzu-Han Chang; Pei-Yu Lin (Gas Science and Engineering, 2023)

Clay nanosheets simultaneously intercalated and stabilized by PEGylated chitosan as drug delivery vehicles for cancer chemotherapy - Hsuan-Jung Huang; Shih-Yu Huang; Tzu-Hao Wang; Tzu-Yun Lin; Nan-Ching Huang; Orion Shih; U-Ser Jeng; Che-Yi Chu; Wen-Hsuan Chiang (Carbohydrate Polymers, 2023)

Lightweight Flexible Polyimide-Derived Laser-Induced Graphenes for High-Performance Thermal Management Applications - Yu-Sheng Hsiao; Cai-Wan Chang-Jian; Tzu-Yen Huang; Ying-Lin Chen; Chung-Wei Huang; Jen-Hsien Huang; Nian-Jheng Wu; Shih-Chieh Hsu; Chih-Ping Chen (Chemical Engineering Journal, 2023)

Gas-phase and PM2.5-bound phthalates in nail salons: characteristics, exposure via inhalation, and influencing factors - Chia-Ling Chang; Hui-Tzu Chen; Chung-Yu Chen; En-Yu Chen; Kuan-Ting Lin; Chien-Cheng Jung (Environmental Science and Pollution Research, 2023)

Impact of salinity origin on microbial communities in saline springs within the Illinois Basin, USA - Linduo Zhao; Hongbo Shao; Li Zhang; Samuel V. Panno; Walton R. Kelly; Tzu‐Yu Lin; Wen‐Tso Liu; Theodore M. Flynn; Peter Berger (Environmental Microbiology, 2022)
Saline springs within the Illinois Basin result from the discharge of deep‐seated evaporated seawater (brine) and likely contain diverse and complex microbial communities that are poorly understood. In this study, seven saline/mineral springs with different geochemical characteristics and salinity origins were investigated using geochemical and molecular microbiological analyses to reveal the composition of microbial communities inhabiting springs and their key controlling factors. The 16S rRNA sequencing results demonstrated that each spring harbours a unique microbial community influenced by its geochemical properties and subsurface conditions. The microbial communities in springs that originated from Cambrian/Ordovician strata, which are deep confined units that have limited recharge from overlying formations, share a greater similarity in community composition and have a higher species richness and more overlapped taxa than those that originated from shallower Pennsylvanian strata, which are subject to extensive regional surface and groundwater recharge. The microbial distribution along the spring flow paths at the surface indicates that 59.8%–94.2% of total sequences in sedimentary samples originated from spring water, highlighting the role of springs in influencing microbiota in the immediate terrestrial environment. The results indicate that the springs introduce microbiota with a high biodiversity into surface terrestrial or aquatic ecosystems, potentially affecting microbial reservoirs in downstream ecosystems.

The influence of climate change on the allocation efficiency of new and tradition energy - Kuei-Ying Huang; Yung-ho Chiu; Tzu-Han Chang; Tai-Yu Lin (Environmental Science and Pollution Research, 2022)

Measuring Heterogeneity in 18F-Fluorodeoxyglucose Positron Emission Tomography Images for Classifying Metastatic and Benign Bone Lesions in Patients with Cervical Cancer - Feng-Yuan Liu; Gigin Lin; Jing-Ren Tseng; Angel Chao; Huei-Jean Huang; Hung-Hsueh Chou; Yu-Chen Chang; Tzu-Chen Yen; Chyong-Huey Lai (Journal of Medical and Biological Engineering, 2021)
Purpose Heterogeneity assessment can be applied for medical imaging analysis. Here, we evaluated first-order and texture analysis (TA) metrics in 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography (PET) imaging for classification of metastatic and benign bone lesions in patients with cervical cancer. Methods The data of 18 F-FDG PET studies performed on a specific PET/CT system from 2016 to 2018 in patients with cervical cancer were retrieved. The data of bone lesions extracted from studies over 2016–2017 and 2018 were used as training and validation datasets, respectively. Metastatic bone lesions were identified in each dataset, with an equal number of benign bone lesions selected. Cuboid volume of interest (VOI) consisting of 3 × 3 × 5 reconstructed voxels was applied for first-order metrics, and cubic VOI consisting of smaller voxels with trilinear interpolation of standardized uptake value (SUV) was adopted for TA metrics. First-order metrics included the maximum SUV (SUVmax) of lesions and the mean voxel SUV and its standard deviation (SUVsd), skewness, and kurtosis in VOI. In total, 4464 TA metrics based on 62 texture features were evaluated. Logistic regression was used for classification with area under the receiver operating characteristic curve (AUC) as the performance measure. Results From the training and validation datasets, 98 and 42 metastatic bone lesions were identified, respectively. SUVsd demonstrated higher performance than did SUVmax in both the training (AUC .798 vs .732, P = .001) and validation (AUC .786 vs .684, P < .001) datasets. Top-performing TA metrics demonstrated significantly higher performance in the training dataset, but not in the validation dataset. Conclusion A simple first-order measure of heterogeneity, SUVsd, was found to be superior to SUVmax for the classification of metastatic and benign bone lesions. Multiple hypothesis testing can result in false-positive findings in TA with multiple features and parameters; careful validation is required.

Detection of Vestibular Schwannoma on Triple-parametric Magnetic Resonance Images Using Convolutional Neural Networks - Tzu-Hsuan Huang; Wei-Kai Lee; Chih-Chun Wu; Cheng-Chia Lee; Chia-Feng Lu; Huai-Che Yang; Chun-Yi Lin; Wen-Yuh Chung; Po-Shan Wang; Yen-Ling Chen; Hsiu-Mei Wu; Wan-You Guo; et al. (Journal of Medical and Biological Engineering, 2021)
Purpose The first step in typical treatment of vestibular schwannoma (VS) is to localize the tumor region, which is time-consuming and subjective because it relies on repeatedly reviewing different parametric magnetic resonance (MR) images. A reliable, automatic VS detection method can streamline the process. Methods A convolutional neural network architecture, namely YOLO-v2 with a residual network as a backbone, was used to detect VS tumors from MR images. To heighten performance, T1-weighted–contrast-enhanced, T2-weighted, and T1-weighted images were combined into triple-channel images for feature learning. The triple-channel images were cropped into three sizes to serve as input images of YOLO-v2. The VS detection effectiveness levels were evaluated for two backbone residual networks that downsampled the inputs by 16 and 32. Results The results demonstrated the VS detection capability of YOLO-v2 with a residual network as a backbone model. The average precision was 0.7953 for a model with 416 × 416-pixel input images and 16 instances of downsampling, when both the thresholds of confidence score and intersection-over-union were set to 0.5. In addition, under an appropriate threshold of confidence score, a high average precision, namely 0.8171, was attained by using a model with 448 × 448-pixel input images and 16 instances of downsampling. Conclusion We demonstrated successful VS tumor detection by using a YOLO-v2 with a residual network as a backbone model on resized triple-parametric MR images. The results indicated the influence of image size, downsampling strategy, and confidence score threshold on VS tumor detection.

Correction to: Genomic Action of Sigma-1 Receptor Chaperone Relates to Neuropathic Pain - Shao-Ming Wang; Nino Goguadze; Yuriko Kimura; Yuko Yasui; Bin Pan; Tzu-Yun Wang; Yoki Nakamura; Yu-Ting Lin; Quinn H. Hogan; Katherine L. Wilson; Tsung-Ping Su; Hsiang-en Wu (Molecular Neurobiology, 2021)
A correction to this paper has been published: 10.1007/s12035-021-02310-3

Genomic Action of Sigma-1 Receptor Chaperone Relates to Neuropathic Pain - Shao-Ming Wang; Nino Goguadze; Yuriko Kimura; Yuko Yasui; Bin Pan; Tzu-Yun Wang; Yoki Nakamura; Yu-Ting Lin; Quinn H. Hogan; Katherine L. Wilson; Tsung-Ping Su; Hsiang-en Wu (Molecular Neurobiology, 2021)
Sigma-1 receptors (Sig-1Rs) are endoplasmic reticulum (ER) chaperones implicated in neuropathic pain. Here we examine if the Sig-1R may relate to neuropathic pain at the level of dorsal root ganglia (DRG). We focus on the neuronal excitability of DRG in a “spare nerve injury” (SNI) model of neuropathic pain in rats and find that Sig-1Rs likely contribute to the genesis of DRG neuronal excitability by decreasing the protein level of voltage-gated Cav2.2 as a translational inhibitor of mRNA. Specifically, during SNI, Sig-1Rs translocate from ER to the nuclear envelope via a trafficking protein Sec61β. At the nucleus, the Sig-1R interacts with cFos and binds to the promoter of 4E-BP1, leading to an upregulation of 4E-BP1 that binds and prevents eIF4E from initiating the mRNA translation for Cav2.2. Interestingly, in Sig-1R knockout HEK cells, Cav2.2 is upregulated. In accordance with those findings, we find that intra-DRG injection of Sig-1R agonist (+)pentazocine increases frequency of action potentials via regulation of voltage-gated Ca2+ channels. Conversely, intra-DRG injection of Sig-1R antagonist BD1047 attenuates neuropathic pain. Hence, we discover that the Sig-1R chaperone causes neuropathic pain indirectly as a translational inhibitor.

Overexpression of a multifunctional β-glucosidase gene from thermophilic archaeon Sulfolobus solfataricus in transgenic tobacco could facilitate glucose release and its use as a reporter - Chih-Hao Huang; Tzu-Ling Huang; Yu-Chang Liu; Ting-Chieh Chen; Shih-Ming Lin; Shyh-Yu Shaw; Ching-Chun Chang (Transgenic Research, 2020)

Household airborne endotoxin associated with asthma and allergy in elementary school-age children: a case–control study in Kaohsiung, Taiwan - Yu-Chuan Yen; Chun-Yuh Yang; Tsu-Nai Wang; Pei-Chun Yen; Chi-Kung Ho; Kristina D. Mena; Tzu-Chi Lee; Kang-Shin Chen; Yuan-Chung Lin; Pei-Shih Chen (Environmental Science and Pollution Research, 2020)
To evaluate the association between the presence of asthma and allergy, and airborne endotoxin in homes of school-age children in Kaohsiung City, Taiwan, with a case–control study design by matching the age and class exposure. Data collection of home visits included an interviewer-administered questionnaire and air sampling of participants’ homes for endotoxin, bacteria, and fungi, as well as temperature and relative humidity measurements. Endotoxin was detected in all air samples with a median value of 0.67 EU m −3 . In the adjusted logistic regression model, household airborne endotoxin was associated with higher prevalence of asthma and allergy; OR = 4.88 (95% CI 1.16–20.55) for Q3 (between 0.67 and 1.97 EU m −3 ) vs. Q1 (< 0.31 EU m −3 ), with statistical significance. Airborne fungi were associated with higher prevalence of asthma and allergy; OR = 4.47 (95% CI 1.13–17.69) for Q3 (between 314 and 699 CFU m −3 ) vs. Q1 (< 159 CFU m −3 ) in adjusted logistic regression models. Airborne endotoxin and fungi were significantly associated with children’s asthma and allergy.

Integrating Patient-Specific Electrocardiogram Signals and Image-Based Computational Fluid Dynamics Method to Analyze Coronary Blood Flow in Patients during Cardiac Arrhythmias - Szu-Hsien Chou; Kuan-Yu Lin; Zhen-Ye Chen; Chun-Jung Juan; Chien-Yi Ho; Tzu-Ching Shih (Journal of Medical and Biological Engineering, 2020)
Purpose The aim of this study was to use the computational fluid dynamics (CFD) method, patient-specific electrocardiogram (ECG) signals, and computed tomography three-dimensional image reconstruction technique to investigate the blood flow in coronary arteries during cardiac arrhythmia. Methods Two patients with premature ventricular contraction-type cardiac arrhythmia and one with atrial fibrillation-type cardiac arrhythmia were investigated. The inlet velocity of the coronary artery in simulation was applied with the measured velocity profile of the left ventricular outflow tract (LVOT) from the Doppler echocardiography. The measured patient central aortic blood pressure waveform was employed for the coronary artery outlet in simulation. The no-slip boundary condition was applied to the arterial wall. Results For the patient with irregular cardiac rhythms (Case I), the coronary blood flow rate under the shortened and lengthened cardiac rhythms were 0.66 and 0.96 mL/s, respectively. In Case II, the maximum velocity at the LVOT under a normal heartbeat was found to be 101 cm/s, whereas the average value was 73 cm/s. In Case III, the patient was also diagnosed with a congenital stenosis problem at the myocardial bridge (MCB) at the LAD. The measured blood flow rate at the MCB of the LAD for the three heartbeats in Case III was found to be 0.68, 1.08, and 1.14 mL/s. Conclusion The integration of patient-specific ECG signals and image-based CFD methods can clearly analyze hemodynamic information for patients during cardiac arrhythmia. The cardiac arrhythmia can reduce the blood flow in the coronary arteries.

Development of Multi-axis Motor Control Systems for Lower Limb Robotic Exoskeleton - Cheng-Tang Pan; Chun-Chieh Chang; Pei-Yuan Sun; Cheng-Lung Lee; Tzu-Chieh Lin; Chung-Kun Yen; Yu-Sheng Yang (Journal of Medical and Biological Engineering, 2019)

Interpreting air temperature generated from urban climatic map by urban morphology in Taipei - Yu-Cheng Chen; Tzu-Wen Lo; Wan-Yu Shih; Tzu-Ping Lin (Theoretical and Applied Climatology, 2019)

Magnesium sulfate inhibits binding of lipopolysaccharide to THP-1 cells by reducing expression of cluster of differentiation 14 - Ya-Ying Chang; Tzu-Yu Lin; Ming-Chang Kao; Tsung-Ying Chen; Ching-Feng Cheng; Chih-Shung Wong; Chun-Jen Huang (Inflammopharmacology, 2019)

The combination of everolimus and terameprocol exerts synergistic antiproliferative effects in endometrial cancer: molecular role of insulin-like growth factor binding protein 2 - Angel Chao; Chiao-Yun Lin; Ren-Chin Wu; Yun-Shien Lee; Li-Yu Lee; Chia-Lung Tsai; Lan-Yan Yang; Hsuan Liu; Shu-Jen Chen; Tzu-Hao Wang; Chyong-Huey Lai (Journal of Molecular Medicine, 2018)

Clinical and microbiological characteristics of peritoneal dialysis-related peritonitis caused by Escherichia coli in southern Taiwan - Wei-Hung Lin; Chin-Chung Tseng; An-Bang Wu; Yu-Tzu Chang; Te-Hui Kuo; Jo-Yen Chao; Ming-Cheng Wang; Jiunn-Jong Wu (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Regulation of H+-pyrophosphatase by 14-3-3 Proteins from Arabidopsis thaliana - Yu-Di Hsu; Yu-Fen Huang; Yih-Jiuan Pan; Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2018)

Insights into the roles of anammox bacteria in post-treatment of anaerobically-treated sewage - Qian Wang; Giin-Yu Amy Tan; Mohammad Azari; Xiaowu Huang; Martin Denecke; Yujie Men; Jin-Young Jung; Satoshi Okabe; Muhammad Ali; Yu-Tzu Huang; Zhuoying Wu; Wai-hung Lo; et al. (Critical Reviews in Environmental Science and Technology, 2018)

Comparative and population genomic landscape of Phellinus noxius : A hypervariable fungus causing root rot in trees - Chia‐Lin Chung; Tracy J. Lee; Mitsuteru Akiba; Hsin‐Han Lee; Tzu‐Hao Kuo; Dang Liu; Huei‐Mien Ke; Toshiro Yokoi; Marylette B. Roa; Mei‐Yeh J. Lu; Ya‐Yun Chang; Pao‐Jen Ann; et al. (Molecular Ecology, 2017)
The order Hymenochaetales of white rot fungi contain some of the most aggressive wood decayers causing tree deaths around the world. Despite their ecological importance and the impact of diseases they cause, little is known about the evolution and transmission patterns of these pathogens. Here, we sequenced and undertook comparative genomic analyses of Hymenochaetales genomes using brown root rot fungus Phellinus noxius , wood‐decomposing fungus Phellinus lamaensis, laminated root rot fungus Phellinus sulphurascens and trunk pathogen Porodaedalea pini . Many gene families of lignin‐degrading enzymes were identified from these fungi, reflecting their ability as white rot fungi. Comparing against distant fungi highlighted the expansion of 1,3‐beta‐glucan synthases in P. noxius , which may account for its fast‐growing attribute. We identified 13 linkage groups conserved within Agaricomycetes, suggesting the evolution of stable karyotypes. We determined that P. noxius has a bipolar heterothallic mating system, with unusual highly expanded ~60 kb A locus as a result of accumulating gene transposition. We investigated the population genomics of 60 P. noxius isolates across multiple islands of the Asia Pacific region. Whole‐genome sequencing showed this multinucleate species contains abundant poly‐allelic single nucleotide polymorphisms with atypical allele frequencies. Different patterns of intra‐isolate polymorphism reflect mono‐/heterokaryotic states which are both prevalent in nature. We have shown two genetically separated lineages with one spanning across many islands despite the geographical barriers. Both populations possess extraordinary genetic diversity and show contrasting evolutionary scenarios. These results provide a framework to further investigate the genetic basis underlying the fitness and virulence of white rot fungi.

Groundwater origins and recharge in a well field near Chien-Shih, Shinchu, Taiwan - Pei-Ying Lin; Louis Loung-Yie Tsai; Chung-Ho Wang; Kuei-Wen Chang; Yu-Yen Sheng; I-Tzu Chu; Wang-Ru Lee (Sustainable Water Resources Management, 2017)

HCV core inhibits hepatocellular carcinoma cell replicative senescence through downregulating microRNA-138 expression - Tzu-Yue Shiu; Yu-Lueng Shih; An-Chieh Feng; Hsuan-Hwai Lin; Shih-Ming Huang; Tien-Yu Huang; Chung-Bao Hsieh; Wei-Kuo Chang; Tsai-Yuan Hsieh (Journal of Molecular Medicine, 2017)

A simple approach for the development of urban climatic maps based on the urban characteristics in Tainan, Taiwan - Yu-Cheng Chen; Tzu-Ping Lin; Chien-Ting Lin (International Journal of Biometeorology, 2017)

The complete mitogenome of sea slug, Nembrotha kubaryana (Mollusca: Polyceridae) - Peng Xiang; Mao Lin; Yu Wang; Gilbert Audira; Sung-Tzu Liang; Chung-Der Hsiao (Conservation Genetics Resources, 2017)

Thrombin/Matrix Metalloproteinase-9-Dependent SK-N-SH Cell Migration is Mediated Through a PLC/PKC/MAPKs/NF-κB Cascade - Chien-Chung Yang; Chih-Chung Lin; Peter Tzu-Yu Chien; Li-Der Hsiao; Chuen-Mao Yang (Molecular Neurobiology, 2016)

Development of single-chain variable fragments (scFv) against influenza virus targeting hemagglutinin subunit 2 (HA2) - Tai-Wei Li; Shu-Fang Cheng; Yen-Tzu Tseng; Yu-Chih Yang; Wen-chun Liu; Sheng-Cyuan Wang; Mei-Ju Chou; Yu-Jen Lin; Yueh Wang; Pei-Wen Hsiao; Suh-Chin Wu; Ding-Kwo Chang (Archives of Virology, 2016)

Interaction of DRD2TaqI, COMT, and ALDH2 genes associated with bipolar II disorder comorbid with anxiety disorders in Han Chinese in Taiwan - Ming-Chuan Hu; Sheng-Yu Lee; Tzu-Yun Wang; Yun-Hsuan Chang; Shiou-Lan Chen; Shih-Heng Chen; Chun-Hsien Chu; Chen-Lin Wang; I Hui Lee; Po See Chen; Yen Kuang Yang; Ru-Band Lu (Metabolic Brain Disease, 2015)

Functional Investigation of Transmembrane Helix 3 in H+-Translocating Pyrophosphatase - Ching-Hung Lee; Yen-Wei Chen; Yun-Tzu Huang; Yih-Jiuan Pan; Chien-Hsien Lee; Shih-Ming Lin; Lin-Kun Huang; Yueh-Yu Lo; Yu-Fen Huang; Yu-Di Hsu; Shih-Chung Yen; Jenn-Kang Hwang; et al. (The Journal of Membrane Biology, 2013)

Responses to booster hepatitis B vaccination are significantly correlated with genotypes of human leukocyte antigen (HLA)-DPB1 in neonatally vaccinated adolescents - Tzu-Wei Wu; Chen-Chung Chu; Tzu-Ying Ho; Huei-Wen Chang Liao; Sheng-Kai Lin; Marie Lin; Hans Hsienhong Lin; Li-Yu Wang (Human Genetics, 2013)

Differential distribution and activation of microglia in the brain of male C57BL/6J mice - Ting-Ting Yang; Chingju Lin; Chao-Tien Hsu; Tzu-Feng Wang; Fang-Yi Ke; Yu-Min Kuo (Brain Structure and Function, 2013)

Application of a web-based remote agro-ecological monitoring system for observing spatial distribution and dynamics of Bactrocera dorsalis in fruit orchards - Joe-Air Jiang; Tzu-Shiang Lin; En-Cheng Yang; Chwan-Lu Tseng; Chia-Pang Chen; Chung-Wei Yen; Xiang-Yao Zheng; Chun-Yi Liu; Ren-Hau Liu; Yu-Fan Chen; Wan-Yi Chang; Cheng-Long Chuang (Precision Agriculture, 2013)

A study of the frequency of methylation of gene promoter regions in colorectal cancer in the Taiwanese population - CHANG-CHIEH WU; JEN-CHUN KUAN; CHIH-HSIUNG HSU; TZU-AN CHEN; CHIEN-AN SUN; TSAN YANG; SHINN-LONG LIN; YU-CHING CHOU (Journal of Genetics, 2013)

Estrogen stimulates the proliferation of human endometrial cancer cells by stabilizing nucleophosmin/B23 (NPM/B23) - Angel Chao; Chiao-Yun Lin; Chia-Lung Tsai; Swei Hsueh; Ying-Yu Lin; Cheng-Tao Lin; Hung-Hsueh Chou; Tzu-Hao Wang; Chyong-Huey Lai; Hsin-Shih Wang (Journal of Molecular Medicine, 2013)

Glycogen synthase kinase-3β inactivation is an intracellular marker and regulator for endotoxemic neutrophilia - Tsan-Tzu Yang; Chia-Ling Chen; Wei-Chieh Lin; Yee-Shin Lin; Po-Chun Tseng; Chia-Yuan Hsieh; Yu-Hong Chen; Wei-Ching Huang; Cheng-Chieh Tsai; Chi-Yun Wang; Chi-Chang Shieh; Chiou-Feng Lin (Journal of Molecular Medicine, 2013)

Albumin prevents reactive oxygen species-induced mitochondrial damage, autophagy, and apoptosis during serum starvation - Shu-Yu Liu; Chia-Ling Chen; Tsan-Tzu Yang; Wei-Ching Huang; Chia-Yuan Hsieh; Wan-Jou Shen; Tsung-Ting Tsai; Chi-Chang Shieh; Chiou-Feng Lin (Apoptosis, 2012)

Molecular epidemiology of Echovirus 30 in Taiwan, 1988–2008 - Guan-Ming Ke; Kuei-Hsiang Lin; Po-Liang Lu; Yi-Chin Tung; Chu-Feng Wang; Liang-Yin Ke; Min-Sheng Lee; Pei-Chin Lin; Hui-Ju Su; Yi-Ying Lin; Tzu-Ping Huang; Jen-Ren Wang; et al. (Virus Genes, 2011)

Anoxia survival in common carp and crucian carp is related to high zinc concentration in tissues - Sen Shyong JENG; Tzu Yung LIN; Ming Shyong WANG; Yu Yin CHANG; Chao Yi CHEN; Chih Chieh CHANG (Fisheries Science, 2008)

Inhibitory effect of trilinolein on endothelin-1-induced c-fos gene expression in cultured neonatal rat cardiomyocytes - Hung-Yu Yang; Ju-Chi Liu; Yen-Ling Chen; Cheng-Hsien Chen; Heng Lin; Jia-Wei Lin; Wen-Ta Chiu; Jin-Jer Chen; Tzu-Hurng Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

Biotic communities of freshwater marshes and mangroves in relation to saltwater incursions: implications for wetland regulation - Hsing-Juh Lin; Kwang-Tsao Shao; Wen-Liang Chiou; Can-Jen W Maa; Hwey-Lian Hsieh; Wen-Lung Wu; Lucia L. Severinghaus; Yu-Tzu Wang (Biodiversity and Conservation, 2003)